Respuesta :

Answer:

D) [tex](x-4.5 )^{2} =16.25[/tex]

Step-by-step explanation:

Explanation

Given that the equation

   x² - 9 x +11 =7

 [tex]x^{2} -\frac{9}{2} (2x) +11=7[/tex]

[tex]x^{2} -\frac{9}{2} (2x) +(\frac{9}{2} )^{2} -(\frac{9}{2}) ^{2}+ 11=7[/tex]

By using (a-b)² = a²-2ab+b²

[tex](x-\frac{9}{2} )^{2} -(\frac{9}{2}) ^{2}+ 11=7[/tex]

[tex](x-\frac{9}{2} )^{2} -(\frac{9}{2}) ^{2}+ 11-7=0[/tex]

[tex](x-\frac{9}{2} )^{2} -(\frac{81}{4}) + 4=0[/tex]

[tex](x-\frac{9}{2} )^{2} +(\frac{-81+16}{4}) =0[/tex]

[tex](x-4.5 )^{2} -16.25 =0[/tex]

Final answer:-

[tex](x-4.5 )^{2} =16.25[/tex]